Smugglers, speculators, and the city in the Ethiopia-Somalia borderlands - Thompson, Daniel K. (Cambridge University Press, 2025)
"Analysing the work of Ethiopian-Somali smugglers and return-migrant investors, this study explores the relationship between cities and borders amid Africa's rapid urbanization. Daniel Thompson describes how African city-dwellers' lives are shaped by global border security regimes, and how they contest these borders in daily urban life"--
2410
Keywords: City and town life / Ethiopia / Jijiga; Smugglers / Ethiopia / Jijiga / Social conditions; Return migrants / Ethiopia / Jijiga / Social conditions; Jijiga (Ethiopia) / Social conditions; Jijiga (Ethiopia) / Economic conditions; Ethiopia / Boundaries; Somalia / Boundaries